Biomechanical Analysis of Segmental Medial Meniscal Transplantation in a Human Cadaveric Model. Issue 12 (October 2021) - Haber, Daniel B.; Douglass, Brenton W.; Arner, Justin W.; Miles, Jon W.; Peebles, Liam A.; Dornan, Grant J.; Vidal, Armando F.; Provencher, CAPT Matthew T.
Background: Meniscal deficiency has been reported to increase contact pressures in the affected tibiofemoral joint, possibly leading to degenerative changes. Current surgical options include meniscal allograft transplantation and insertion of segmental meniscal scaffolds. Little is known about segmental meniscal allograft transplantation. Purpose: To evaluate the effectiveness of segmental medial meniscal allograft transplantation in the setting of partial medial meniscectomy in restoring native knee loading characteristics. Study Design: Controlled laboratory study. Methods: Ten fresh-frozen human cadaveric knees underwent central midbody medial meniscectomy and subsequent segmental medial meniscal allograft transplantation. Knees were loaded in a dynamic tensile testing machine to 1000 N for 20 seconds at 0°, 30°, 60°, and 90° of flexion. Four conditions were tested: (1) intact medial meniscus, (2) deficient medial meniscus, (3) segmental medial meniscal transplant fixed with 7 meniscocapsular sutures, and (4) segmental medial meniscal transplant fixed with 7 meniscocapsular sutures and 1 suture fixed through 2 bone tunnels. Submeniscal medial and lateral pressure-mapping sensors assessed mean contact pressure, peak contact pressure, mean contact area, and pressure mapping. Two-factor random-intercepts linear mixed effects models compared pressure and contact area measurements among experimental conditions. Results: The meniscal-deficient state demonstrated a significantly higher mean contact pressure than all other testing conditions (mean difference, ≥0.35 MPa; P < .001 for all comparisons) and a significantly smaller total contact area as compared with all other testing conditions (mean difference, ≤140 mm 2 ; P < .001 for all comparisons). There were no significant differences in mean contact pressure or total contact area among the intact, transplant, or transplant-with-tunnel groups or in any outcome measure across all comparisons in the lateral compartment. No significant differences existed in center of pressure and relative pressure distribution across testing conditions. Conclusion: Segmental medial meniscal allograft transplantation restored the medial compartment mean contact pressure and mean contact area to values measured in the intact medial compartment. Clinical Relevance: Segmental medial meniscal transplantation may provide an alternative to full meniscal transplantation by addressing only the deficient portion of the meniscus with transplanted tissue. Additional work is required to validate long-term fixation strength and biologic integration.